Simulation of decentralized flow control protocol for integrated networks with partially observed voice traffic - Lo, Boon Lian. (2009)
For Broadband ISDN (Integrated Services Digital Network), the problem of mixed and bursty traffic sources have prompted many research topics into flow and congestion controls. Several authors suggested different flow control schemes in order to make the network satisfy the user requirements for communication quality. Some authors use theoretical analytical approaches to analyse the effect of each scheme on the performance of the network. For this project, we develop a discrete event simulation to model the flow control of Asynchronous Transfer Mode (ATM) networks. Our computer simulation results in the case studies of various control schemes were compared with the results derived by the analytical results.